Experimental and numerical analysis of compressed cold-formed steel elements with sigma-plus cross-sections subjected to fire - Escudeiro, André Filipe Ferreira (2016)
Dissertação de Mestrado Integrado em Engenharia Civil apresentada à Faculdade de Ciências e Tecnologia